Tindak Tutur dan Fungsi Tuturan Ekspresif dalam Acara Rumah Perubahan Rhenald Kasali - Cintya Nurika Irma (SAP (Susunan Artikel Pendidikan), 2017)
The research, entitled "Speech Act and Function of Expressives in a program Rumah Perubahan Rhenald Kasali", is intended to describe the use of speech actin the form of locutionary, illocutionary, perlocutionary acts and the use of expressives to congratulate, thank, criticize, complain, wonder, praise and apologize by speakers to interlocutors in a program Rumah Perubahan Rhenald Kasali. The method used in this research is descriptive qualitative method with observing, recording and taking note techniques. Based on the result of the research, there are 10 speech acts and 11 expressives found in the program,with the speech act consisting of 3 locutionary acts, 2 illocutionary acts and 5 perlocutinary acts and with the expressive including 2 expressions of congratulating, 2 expressions of thanking, 1 expression of criticizing, 1 expression of complaining, 2 expressions of wondering, 2 expressions ofpraising and 1 expression of apologizing.